Immigration Policy and Remittance Behaviour - Matloob Piracha; Massimiliano Tani; Guy Tchuente (Global Labor Organization (GLO), 2017)
This paper analyses the impact of a change in Australia's immigration policy, introduced in the mid-1990s, on migrants' remittance behaviour. More precisely, we compare the remittance behaviour of two cohorts who entered Australia before and after the policy change, which consists of stricter entry requirements. Our empirical strategy uses conditional difference-in-differences in the presence of interactive fixed-effects. We first show that Bai's (2009) least squares estimator and conditional difference-in-differences are biased if used on their own. We then derive conditions that are required to obtain a consistent estimator using a combination of conditional difference-in-differences and Bai's (2009) least squares estimator. The results indicate that those who entered under more stringent conditions - the second cohort - have a higher probability to remit than those in the first cohort, though the policy change has no discernible effect on the level of remittances.
Keywords: C13; F22; F24; J61; 330; Immigration; Treatment effect; difference-in-differences